Enhancement of Migration and Tenogenic Differentiation of Macaca Mulatta Tendon-Derived Stem Cells by Decellularized Tendon Hydrogel - Ning, Liang-Ju; Zhang, Ya-Jing; Zhang, Yan-Jing; Zhu, Min; Ding, Wei; Jiang, Yan-Lin; Zhang, Yi; Luo, Jing-Cong; Qin, Ting-Wu (Frontiers in Cell and Developmental Biology, 2021)
Decellularized tendon hydrogel from human or porcine tendon has been manufactured and found to be capable of augmenting tendon repair in vivo. However, no studies have clariﬁed the effect of decellularized tendon hydrogel upon stem cell behavior. In the present study, we developed a new decellularized tendon hydrogel (T-gel) from Macaca mulatta, and investigated the effect of T-gel on the proliferation, migration and tenogenic differentiation of Macaca mulatta tendon-derived stem cells (mTDSCs). The mTDSCs were first identiﬁed to have universal stem cell characteristics, including clonogenicity, expression of mesenchymal stem cell and embryonic stem cell markers, and multilineage differentiation potential. Decellularization of Macaca mulatta Achilles tendons was conﬁrmed to be effective by histological staining and DNA quantification. The resultant T-gel exhibited highly porous structure or similar nanoﬁbrous structure and approximately swelling ratio compared to the collagen gel (C-gel). Interestingly, stromal cell-derived factor-1 (SDF-1) and ﬁbromodulin (Fmod) inherent in the native tendon extracellular matrix (ECM) microenvironment were retained and the values of SDF-1 and Fmod in the T-gel were significantly higher than those found in the C-gel. Compared with the C-gel, the T-gel was found to be cytocompatible with NIH-3T3 fibroblasts and displayed good histocompatibility when implanted into rat subcutaneous tissue. More importantly, it was demonstrated that the T-gel supported the proliferation of mTDSCs and signiﬁcantly promoted the migration and tenogenic differentiation of mTDSCs compared to the C-gel. These ﬁndings indicated that the T-gel, with its retained nanofibrous structure and some bioactive factors of native tendon ECM microenvironment, represents a promising hydrogel for tendon regeneration.